Indonesia Economic Quarterly, October 2017 : Closing the Gap - World Bank (World Bank, Washington, DC, 2018)
Indonesia’s real gross domestic product (GDP) expanded by 5.0 percent yoy in Q2 2017, unchanged from Q1. Growth rates have been steady at around 5 percent since Q1 2014, lower than those recorded at the beginning of the decade. While this growth rate places Indonesia among the fastest-growing large economies in the world, the lack of an acceleration is a matter of concern, considering the favorable external environment and domestic policy reform momentum. Government consumption is expected to increase in 2018, but deficits will remain contained due to enhanced revenue performance linked to economic growth and tax reforms. It is critical to maintain reform momentum as gaps in physical and human capital, as well as institutional quality, are still significant. The government has begun to take measures, but accelerating the pace of private sector investments to close the infrastructure gap with emerging economies will require further efforts.